PENERAPAN DIVERSI DALAM PENYELESAIAN PERKARA PIDANA ANAK YANG BERHADAPAN DENGAN HUKUM PADA TINGKAT PENUNTUTAN (Studi Pada Kejaksaan Negeri Payakumbuh) - Ibrahim Khalil (Program Magister Ilmu Hukum Universitas Ekasakti, 2019)
Diversion according to Article 1 number 7 of Act Number 11 of 2012 concerning the ChildCriminal Justice System is the transfer of settlement of Child cases from criminal justiceprocesses to processes outside of criminal justice. Diversion is to settle criminal casesinvolving children as perpetrators and children as victims. The implementation ofdiversion is intended to avoid negative effects and stigmatization of children so thatchildren are expected to return to the social environment fairly. The Payakumbuh DistrictAttorney also conducted a diversion of cases of criminal acts of violence against childrenthrough a process that turned out to be not as simple as expected, so that it encounteredobstacles in resolving cases of children facing the law.